First screening of biocides, persistent organic pollutants, pharmaceutical and personal care products in Antarctic phytoplankton from Deception Island by FT-ICR-MS. (July 2021) - Duarte, Bernardo; Gameiro, Carla; Matos, Ana Rita; Figueiredo, Andreia; Silva, Marta Sousa; Cordeiro, Carlos; Caçador, Isabel; Reis-Santos, Patrick; Fonseca, Vanessa; Cabrita, Maria Teresa
Abstract: In recent years, the Antarctic territory has seen a rise in the number of tourists and scientists. This has led to an increase in the anthropogenic footprint in Antarctic ecosystems, namely in terms of emerging contaminants, such as Biocides, Persistent Organic Pollutants (POPs) as well as Pharmaceutical and Personal Care Products (PPCPs). Yet scarce information on the presence of these emerging contaminants is available for trophic compartments, especially the phytoplankton community. Using high resolution Fourier-transform ion cyclotron-resonance mass spectrometry (FT-ICR-MS), an untargeted screening of the metabolome of the phytoplankton community was performed. Seventy different contaminant compounds were found to be present in phytoplankton collected at two sites in Port Foster Bay at Deception Island. These emerging contaminants included 1 polycyclic aromatic hydrocarbon (PAH), 10 biocides (acaricides, fungicides, herbicides, insecticides and nematicides), 11 POPs (flame retardants, paints and dyes, polychlorinated biphenyl (PCB), phthalates and plastic components), 5 PCPs (cosmetic, detergents and dietary compounds), 40 pharmaceutical compounds and 3 illicit drugs. Pharmaceutical compounds were, by far, the largest group of emerging contaminants found in phytoplankton cells (anticonvulsants, antihypertensives and beta-blockers, antibiotics, analgesic and anti-inflammatory drugs). The detection of several of these potentially toxic compounds at the basis of the marine food web has potentially severe impacts for the whole ecosystem trophic structure. Additionally, the present findings also point out that the guidelines proposed by the Antarctic Treaty and Protocol on Environmental Protection to the Antarctic Treaty should be revisited to avoid the proliferation of these and other PPCPs in such sensitive environments. Highlights: In recent years, there has been an increase in the anthropogenic footprint in Antarctic ecosystems. 70 Persistent Organic Pollutants were detected in phytoplankton cells from Deception Island. Pharmaceutical compounds were, the most abundant group of emerging contaminants detected. Phytoplankton contamination with these toxic compounds has severe impacts for the whole ecosystem.